PENGARUH KAPABILITAS ORGANISASI TERHADAP IMPLEMENTASI STRATEGI OPERASI DALAM MENINGKATKAN KINERJA PERUSAHAAN (STUDI KASUS PADA DEPARTMENT PROCESS PLANT PT VALE INDONESIA TBK) - Dian Tri Saputri; Nurdin Brasit; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Performance appraisal is the periodic determination of operational effectiveness of a company. This study aims to Analyze the effect of process capability on the implementation of operating strategy, analyze the effect of process capability to operational performance, and analyze the influence of operational strategy implementation on operational performance. The approach used in this research is explanatory approach which explains the causality relationship that is to identify causal relationship between variables, the researcher looks for the real type of facts to help understand and predict the relationship. The results showed that partially each of the variables Improvement, Collaboration, Responsiveness, Reconfiguration, and Innovation positively affect the Implementation of Operation Strategy. Improvement, Collaboration, Responsiveness, Reconfiguration, and Innovation positively affect the Company Performance. Simultaneously Implementation of Operation Strategy has a positive effect on Company Performance.